ECONOMIC ANALYSIS OF ALTERNATIVE FEEDING APPLICATIONS IN KOI FISH CULTURE (Cyprinus carpio L.) - Heny - Suprastyani (Journal of Innovation and Applied Technology, 2017)
This study aimed to analyze the economic feasibility of koi fish (Cyprinus carpio L) culture with the use of alternative feed plus probiotics, compared with a koi fish culture with use of comercial feed. The method used is descriptive method with qualitative and quantitative analysis. The calculations show that the koi fish culture with use of alternative feed plus probiotics comparing with koi fish culture with use commercial feed, respectively, had profit = 6.28 million rupiahs and 25.971 million rupiahs / year; Rentability = 30.63 and 126.69%; R / C ratio = 1.14 and 1.59; Break Event Point Unit = 307.43 and 128 fish; and payback period = 3.26 and 0.10 years. It can be concluded that the the koi fish culture in the village of Lumbang with the use of alternative feed plus probiotics more efficient, profitable, and deserves to be run and developed  by fish farmers in the village of Lumbang, compared with koi fish culture with the use of the commercial feed